2012
DOI: 10.1007/s11832-012-0454-7
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic surgery and mobility goals for children with cerebral palsy GMFCS level IV: What are we setting out to achieve?

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
1
18
1
3
Order By: Relevance
“…Over 90% of these children have musculoskeletal impairments that result in slower and less coordinated motor actions ( Abel and Damiano, 1996 , Johnson et al, 1997 , Norlin and Odenrick, 1986 ). These observations have fueled the original belief that the motor aberrations seen in children with CP primarily originated in the musculoskeletal machinery ( Pin et al, 2006 , Moreau et al, 2012 , Blumetti et al, 2012 , Dreher et al, 2012 , Taylor et al, 2013 ). However, this hypothesis has been significantly challenged in recent years, as it is becoming widely recognized that the white matter damage seen in these children likely impacts activity within the key brain networks that are involved in processing sensory information and the production of motor actions (cf.…”
Section: Introductionmentioning
confidence: 93%
“…Over 90% of these children have musculoskeletal impairments that result in slower and less coordinated motor actions ( Abel and Damiano, 1996 , Johnson et al, 1997 , Norlin and Odenrick, 1986 ). These observations have fueled the original belief that the motor aberrations seen in children with CP primarily originated in the musculoskeletal machinery ( Pin et al, 2006 , Moreau et al, 2012 , Blumetti et al, 2012 , Dreher et al, 2012 , Taylor et al, 2013 ). However, this hypothesis has been significantly challenged in recent years, as it is becoming widely recognized that the white matter damage seen in these children likely impacts activity within the key brain networks that are involved in processing sensory information and the production of motor actions (cf.…”
Section: Introductionmentioning
confidence: 93%
“…In ambulatory patients (GMFCS levels I, II and III), SEMS is widely accepted as the gold standard for improving gait. [9,22] It has been reported that surgical treatment is planned more accurately and the results are more successful by performing static and dynamic examination together. [4,14] A number of other studies in the orthopedic literature have also accepted a significant positive change in the level of GMFCS after SEMS.…”
Section: Discussionmentioning
confidence: 99%
“…Only one patient maintained an FMS score of 2, 1, 1 at 2 years' follow-up. Most children lost their ability to do supported walking and standing transfers at 2 years' post-surgery [29]. Some external factors are known to influence the outcomes after OS, including post-operative rehabilitation, use of orthotic devices, pain-controlling strategies, adequate tone control, and presence of comorbidities [91].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the role of orthopaedic surgery for children with CP at GMFCS level IV is limited to the treatment and prevention of spastic hip disease and scoliosis [29].…”
mentioning
confidence: 99%